Review ArticleCurrent salt reduction policies across gradients of inequality-adjusted human development in the WHO European region: minding the gaps. Issue 8 (8th August 2013) - Rodriguez-Fernandez, Rodrigo; Siopa, Margarida; Simpson, Sarah J; Amiya, Rachel M; Breda, Joao; Cappuccio, Francesco P
Abstract Objective To assess current salt† reduction policies in countries of the WHO European Region against the backdrop of varying levels of human development adjusted for income, education and health (longevity) inequalities. Design Population-based, cross-sectional study, with data gathered through systematic review of relevant databases and supplementary information provided by WHO Nutrition Counterparts. Setting Member States of the WHO European Region. Subjects Inequality-adjusted Human Development Index scores were analysed against assessed levels of development and implementation of national nutrition policies and initiatives targeting population-level salt reduction. Results Within the WHO European Region, Inequality-adjusted Human Development Index values among countries with no existing salt reduction initiatives (mean 0·643 (se 0·022)) were significantly lower than among those with either partially implemented/planned salt initiatives (mean 0·766 (se 0·017), P < 0·001) or fully implemented salt initiatives (mean 0·780 (se 0·021), P < 0·001). Conclusions Where salt reduction strategies are implemented as an integral part of national policy, outcomes have been promising. However, low- and middle-income countries may face severe resource constraints that keep them from emulating more comprehensive strategies pursued in high-income countries. Care must be taken to ensure that gaps are not inadvertently widened by monitoring differential policy impacts of salt policies, particularly regarding trade flows.